2019
DOI: 10.12982/cmujns.2019.0015
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Fe(II) Solution by Sugarcane Bagasse and Activated Carbon Prepared from Sugarcane Bagasse

Abstract: Fe(II) contaminant in groundwater is one of the most important in the environmental pollutions as it affects the taste, esthetic quality of the water and turns the color of the water to red-brown. Moreover, when Fe(II) contaminate in large amounts, it is harmful to health. The objective of this study was to evaluate the performance of Fe(II) removal in aqueous solution by the low-cost adsorbents namely, sugarcane bagasse (SB) and activated carbon prepared from sugarcane bagasse (ACSB). The two adsorbents were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The findings are supported by Shah et al (2020), where the transmittance % of the samples after removal was higher than before. Further, Sawasdee et al (2020) also reported that the transmittance % of the IR spectrum increased after the removal process. Hence, this verified that there was an interaction between the contaminants and the active surface of the AC sample (Dula et al 2014).…”
Section: Fourier Transform Infrared Spectroscopy Analysismentioning
confidence: 91%
“…The findings are supported by Shah et al (2020), where the transmittance % of the samples after removal was higher than before. Further, Sawasdee et al (2020) also reported that the transmittance % of the IR spectrum increased after the removal process. Hence, this verified that there was an interaction between the contaminants and the active surface of the AC sample (Dula et al 2014).…”
Section: Fourier Transform Infrared Spectroscopy Analysismentioning
confidence: 91%